Effects Science Teaching Material with Case-based Learning Improving Critical Thinking - Fembriani, Fembriani; Lehan, Anndriyani Afliyanti Dua; Nawa, Netty Elisabeth Antoneta; Kota, Martha Kristin (Widyagogik, 2025)
This research aims to study effectiveness of the science teaching material with a case-based learning approach towards the critical thinking skill. This study belongs to the experimental research with  pretest-post test control group design. The research samples were 66 students at semester 1 in the Study Program of Elementary School Teacher Education, Nusa Cendana University. The research showed the average results of post test control at 59 and experiment at 87. The result of the paired sample t-test in post-test control and experiment was Sig. value at 0.000, indicating a significantly average difference between control and experiment class results. Percentage of the student response towards implementation of the teaching material was 94%. Conclusion of this research shows that the use of science teaching material with the case-based learning approach is effective for improving the critical thinking skill  while the student response is in a very effective category.